1992
DOI: 10.1021/je00008a015
|View full text |Cite
|
Sign up to set email alerts
|

Conductance of lithium and sodium perchlorates and of some quaternary ammonium halides and perchlorates in a propylene carbonate + tetrahydrofuran mixture at 25 .degree.C

Abstract: The electrical conductances of lithium and sodium perchlorates and of some quaternary ammonium halides and perchlorates in propylene carbonate (PC) + tetrahydrofuran (THF) (1:l in volume) have been measured at 25 OC. The conductance data were analyzed by a minimization technique using the complete form of the Fuoss/Hsia (F/H) equation. All electrolytes were found to be anomalous in showing unusually higher molar conductances than in each solvent alone. The effect of the variation of the three parameters KA, A,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Moreover, PC is an excellent solvent for many organic and inorganic materials in such applications as surface cleaners, degreasers, dyes, plastics, batteries, and natural gas. It is also widely used for lithium battery electrolytes because of its high relative permittivity, high boiling point, and good solubilizing power for lithium salts. A comprehension of its local liquid structure and its interaction with water in the PC-rich region of the phase diagram would be interesting to deeper understand its peculiar and anomalous properties and its potentiality as a solvent and reaction medium. Moreover, PC has been studied but mainly with the aim of characterizing some electrochemical properties in the presence of electrolytes …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PC is an excellent solvent for many organic and inorganic materials in such applications as surface cleaners, degreasers, dyes, plastics, batteries, and natural gas. It is also widely used for lithium battery electrolytes because of its high relative permittivity, high boiling point, and good solubilizing power for lithium salts. A comprehension of its local liquid structure and its interaction with water in the PC-rich region of the phase diagram would be interesting to deeper understand its peculiar and anomalous properties and its potentiality as a solvent and reaction medium. Moreover, PC has been studied but mainly with the aim of characterizing some electrochemical properties in the presence of electrolytes …”
Section: Introductionmentioning
confidence: 99%
“…We are engaged in a systematic study on the thermodynamic properties of esters of carbonic acids, which are indicated in the literature to have good properties as solvents in a variety of extractions of industrial interest and in pharmaceutical (1,2) and electrochemical studies (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, little information was available for symmetric polyvalent (Molinou and Tsierkezos, 2001;Molinou, 2000, 2006) and unsymmetric electrolytes (K 2 SO 4 , Na 2 SO 4 , Cd(NO 3 ) 2 , CdCl 2 , CaCl 2 , Ca(NO 3 ) 2 , CoCl 2 , and Zn(NO 3 ) 2 ) in nonaqueous (e.g., Gibson et al, 2006;Pura, 2007) or mixed solvents (Fujii et al, 2006;Qiao et al, 2008). In mixed nonaqueous solvents, the study of complexation were almost limited to symmetric univalent electrolytes in binary mixtures containing PC and selected dipolar aprotic solvents such as THF (Al-Najar et al, 1992), EC (Srivastava and Samant, 1994), DMSO (Srivastava and Shankar, 1998), AN (Barthel et al, 1999), and so forth. Qiao et al (2008) determined the ion association of LiBF 4 in MEC + DMC and MEC + AN, and Fujii et al (2006) measured the formation constants of cobalt chloride ion pairs (CoCl + , CoCl − 3 , CoCl 2− 4 , CoCl (2−n)+ n , n = 1-4) in DMF + NMF.…”
Section: Downloaded By [Northeastern University] At 07:36 27 Novembermentioning
confidence: 99%
“…DMSO + PC (20-80%; 25 • C) [Srivastava and Shankar, 1998] Perchlorate 2-methoxyethanol + H 2 O (20-80%; 25 • C) [Das and Hazra, 1998]. PC -Najar et al, 1992]. MEK + Ac (0-100%; 25 • C) [Niazi, 1988].…”
Section: Downloaded By [Northeastern University] At 07:36 27 Novembermentioning
confidence: 99%
See 1 more Smart Citation